The effects of Lactobacillus plantarum addition to robusta coffee (Coffea canephora L.) during wet fermentation - YULIANA RENI SWASTI; LAI PENG LEONG; EKAWATI PURWIJANTININGSIH; FRANCISCUS SINUNG PRANATA (Society for Indonesian Biodiversity, 2024)
Abstract. Swasti YR, Leong LP, Purwijantiningsih E, Pranata FS. 2024. The effects of Lactobacillus plantarum addition to robusta coffee (Coffea canephora L.) during wet fermentation. Biodiversitas 25: 3132-3140. Robusta coffee from the slopes of Merapi volcano in Indonesia is processed using a wet fermentation method. Its chemistry compound quality depends on the spontaneous microorganism during wet fermentation. This study aimed to investigate the effect of Lactobacillus plantarum in increasing the antioxidant activity and reducing the concentration of caffeine and mutagenic compounds during fermentation. After fermentation, the chemical compounds of green and roasted beans were determined. The furfuryl alcohol compound and protein were only analyzed in the roasted beans. Results showed that the addition of L. plantarum was able to alter the Chlorogenic Acid (CGA) concentration of robusta coffee. The concentration of CGA in the unroasted robusta coffee with the addition of L. plantarum after 6-hour of fermentation tends to be higher than in without the addition of L. plantarum, while caffeine concentration was slightly reduced. The CGA in unroasted and roasted coffee with 12-hour fermentation period resulted in the highest radical ABTS scavenging capacity. Moreover, caffeine in unroasted and roasted coffee with 6-hour fermentation period showed high radical ABTS scavenging capacity. The furfuryl alcohol content tends to be stable.